2017
DOI: 10.1111/acer.13446
|View full text |Cite
|
Sign up to set email alerts
|

Acute Alcohol Binge Deteriorates Metabolic and Respiratory Compensation Capability After Blunt Chest Trauma Followed by Hemorrhagic Shock-A New Research Model

Abstract: This study indicates that alcohol limits the metabolic and respiratory compensation capability, thereby promoting mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 38 publications
(59 reference statements)
0
14
0
Order By: Relevance
“…Zehtabchi et al reported a higher prevalence of lactic acidosis in ethanol-intoxicated patients than in other patients in the emergency department [ 27 ]. Respiratory acidosis is related to depression in respiratory rate [ 28 ], whereas metabolic acidosis may be related to alcoholic ketoacidosis associated with an increased anion gap [ 29 ] and renal dysfunction [ 24 ], both of which were observed in our study. Because we used mechanical ventilation to keep PaCO 2 within normal ranges, we cannot exclude the possibility that respiratory acidosis may have occurred in our model.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Zehtabchi et al reported a higher prevalence of lactic acidosis in ethanol-intoxicated patients than in other patients in the emergency department [ 27 ]. Respiratory acidosis is related to depression in respiratory rate [ 28 ], whereas metabolic acidosis may be related to alcoholic ketoacidosis associated with an increased anion gap [ 29 ] and renal dysfunction [ 24 ], both of which were observed in our study. Because we used mechanical ventilation to keep PaCO 2 within normal ranges, we cannot exclude the possibility that respiratory acidosis may have occurred in our model.…”
Section: Discussionmentioning
confidence: 79%
“…In addition to earlier hypotension, acutely intoxicated animals also showed an earlier onset of lactic acidosis. In a rat blunt (thoracic) chest trauma and hemorrhagic shock model, Wagner et al showed that acute ethanol intoxication induced both respiratory and metabolic acidosis [ 24 ]. In guinea pigs with hemorrhagic shock, acute ethanol intoxication also exacerbated lactic acidosis [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the context of these studies, ethanol experience in rodents produces respiratory acidosis and metabolic acidosis that is accompanied by respiratory depression [ 56 ]. For example, it is likely that chronic ethanol experience will lead to brain tissue acidification and carbon dioxide retention [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the context of these studies, ethanol experience in rodents produces respiratory acidosis and metabolic acidosis that is accompanied by respiratory depression [ 56 ]. For example, it is likely that chronic ethanol experience will lead to brain tissue acidification and carbon dioxide retention [ 56 , 57 ]. These physiological changes by ethanol may induce increased tissue CA activity to maintain acid-base balance by rapid catalytic hydration of carbon dioxide to carbonic acid [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…The right femoral artery was cannulated with polyethylene tubing for continuous blood pressure measurement. For the bilateral lung contusion the animals placed and a standardized air blast wave was directed to the thorax (TxT) of the animals as described before ( 39 ). After a short stabilization phase, the left jugular vein and the right carotid artery were cannulated.…”
Section: Methodsmentioning
confidence: 99%